EPS8L2 drives colorectal cancer cell proliferation and migration via YBX1-dependent activation of G3BP2 transcription - Yimeng Duan; Peixian Li; Yanmei Yang; Guanghua Wu; Hao Xing; Hong Chen; Liangbo Zhao; Lei Liu; Xiao Sun; Shuiling Jin; Luyun He; Benyu Liu (Cell Death and Disease)
Abstract Colorectal cancer (CRC) remains a leading cause of cancer-related mortality worldwide, characterized by molecular heterogeneity and limited therapeutic options. Here, we identified EPS8L2 as a novel driver of colorectal tumorigenesis. EPS8L2 is significantly upregulated in CRC tissues and negatively correlated with patients’ prognosis. Functionally, upregulation of EPS8L2 promotes proliferation and metastasis of CRC cells in vitro and in vivo, and vice versa. Similarly, EPS8L2 overexpression promotes patient-derived organoids growth. Mechanistically, EPS8L2 increases YBX1 phosphorylation by enhancing its interaction with phosphokinase S6K1. Phosphorylated YBX1 translocates into nucleus and initiates G3BP2 transcription, leading to activation of the MAPK signaling pathway. Moreover, knockout of Eps8l2 impairs CRC tumorigenesis in the AOM/DSS induced mouse model. In summary, we revealed a novel EPS8L2-YBX1-G3BP2 regulatory axis involved in CRC progression, which provides a new theoretical basis for tumor therapy.